Du droit de propriété : certaines de ses dimensions méconnues - Frenette, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The owner's power over his property has for centuries been the object of a tripartite analysis (jus utendi, jus fruendi, jus abutendi) leaving little or no doubt as to the contents of the most important of all real rights. In the author's opinion, the traditional analysis is incomplete, since it does not account for a basic, subsisting element underlying these three attributes of ownership.